Diabetes Mellitus and its concommitant disorders in Afghan Refugees Residing in Peshawar Pakistan - Abu sofeh, Ala Sobhi; Khan, Abdus Sattar; Khan, Mudassir Ahmad (Journal of Postgraduate Medical Institute, 2011)
To determine the frequency of diabetes melitus and its concomitant disorders in Afghan Refugees. This study was carried out to see the prevalence of a number of disease in Afghan Refugees attending different dispensaries and hospitals under Red Cross Control, located in Peshawar, Pakistan. The disease that were looked for were diabetes mellitus, hepatitis, nephritis, hyperlipidemia and diabetes mellitus with concomitant disorders like hepatitis, nephritis and hyperlipidemia. A total of 456 Afghan patients were seen with non insulin dependent diabetes mellitus, hepatitis, nephritis, hyperlipidemia and diabetes mellitus with concomittant disorders like hepatitis, nephritis and hyperlipidemia attending differnt dispensaries and hospitals under RCC, located in Pesahwar. during a two years study period. Blood glucose, total lipids, cholesterol, triglycerides total and direct bilirubin, urea, creatinine, uric acid, asparate aminotransferase (AST), Alanine aminotyransferase (ALT) and alkaline phasphatase (ALP) were determined by colorimetric method. The frequency of non insulin dependent diabetes mellitus was found to be very high in Afghan Refugees in Peshawar then the rest of the diseases and the percentage of male patients in all groups of diseases subjects in higher than the female.